The influence of contemporary sales determinants and moderating effect of customer organisational citizenship behaviour on sales performance in Singapore’s business-to-consumer market - Tham, Weng Kin (Nanyang Technological University, 2024)
With the significant transformation of the sales environment in recent years, there is a pressing need to identify and understand the contemporary drivers of sales performance, particularly in Singapore’s business-to-consumer (B2C) context. This study investigates the influence of contemporary sales determinants and Customer Organisational Citizenship Behaviour (COCB) on sales performance in Singapore's B2C market using a mixed-method approach. The first phase of the study began with qualitative interviews of nine sales subject matter experts to identify five key sales determinants – Interpersonal Skill, Salesmanship, Selling-related Knowledge, Adaptive Selling and Customer Orientation. In the second phase, quantitative analyses using responses from 93 active salespeople tested the relationships between the five determinants, COCB, and sales performance. The hierarchical regression analyses revealed that all five identified key sales determinants significantly predicted sales performance. However, COCB was found to have a non-significant moderating effect on the relationship between the sales determinants and sales performance. The findings of this study highlight key competencies that salespeople need to succeed in an increasingly competitive marketplace and extend to sales training and management practices, advocating for a holistic approach that integrates key sales competencies and adapts to the evolving demands of the marketplace.